Метод аналізу стану відповідності UX/UI сайтів аграрних фірм України - Мєшков С. О.; Mieshkov S. O. (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті запропоновано комплексний метод аналізу стану відповідності UX/UI сайтів аграрних фірм України сучасним стандартам і очікуванням користувачів. Методика поєднує інструментальні вимірювання через WCAG-аудит, експертні перевірки мобільної адаптивності та юзабіліті за евристиками Нільсена, а також оцінку галузевої функціональності, технічної якості й спеціалізованих аспектів. Результати агрегуються в єдиній 110-бальній шкалі з прозорими правилами нарахування та вагами категорій. Проведено апробацію методу на вибірці семи українських аграрних компаній, яка виявила середній рівень відповідності 48 відсотків. Найкращі результати показані в категорії юзабіліті, найгірші в спеціалізованих методах адаптації для польових умов. Сформовано практичні рекомендації для короткострокового, середньострокового та довгострокового покращення показників відповідності. /// EN: This research presents a comprehensive methodological framework for assessing UX/UI compliance of Ukrainian agribusiness websites against contemporary standards and user expectations. The methodology represents a significant advancement in digital quality evaluation specifically tailored for the agricultural sector, addressing the critical gap between general web assessment tools and domain-specific requirements of agribusiness enterprises. The approach systematically combines multiple evaluation dimensions through a structured six-category assessment system totaling 110 points, with each category weighted according to its relative importance for agricultural business contexts. The accessibility evaluation employs established WCAG 2.1 standards using four complementary automated tools including axe DevTools, Google Lighthouse, WAVE Tool, and Pa11y, providing comprehensive coverage of digital accessibility requirements that are increasingly mandated by European legislation. Mobile responsiveness assessment specifically addresses field conditions unique to agricultural operations, including touch interface optimization for gloved hands, screen visibility under bright sunlight, and performance constraints of rural network infrastructure. Usability evaluation adapts Nielsen's classical heuristic principles to agricultural business contexts, examining navigation patterns, information architecture, and conversion pathways relevant to B2B agricultural transactions. Technical quality inspection covers code validation, security implementation, and search engine optimization factors critical for international market visibility. Specialized assessment methods address multilingual support requirements for export markets, digital literacy considerations for diverse user populations, and offline functionality needs for unstable connectivity environments. The methodology was validated through pilot implementation across seven Ukrainian agribusiness companies representing different scales and specializations within the sector. Results revealed an average compliance rate of 48 percent, indicating substantial improvement potential across all evaluated categories. Performance analysis identified systematic deficiencies in accessibility compliance, mobile optimization for field conditions, and specialized agricultural functionality implementation.
A method for assessing UX/UI compliance of Ukrainian agribusiness websites
Keywords: UX/UI; аграрний сектор; веб-сайт; юзабіліті; цифровий маркетинг; agribusiness; website; usability; digital marketing